Send me an update : - Mackey, Daphne (McGraw-Hill, 2006)
This book is useful for the intermediate and advanced learners with the expansion of global business and the strong role that English plays in it. Its communicating clearly in written English has become essential. The book guides the learners to proficiency in complex writing tasks such as reports and recommendations.